Characterizations of Chitosan-based polymer electrolyte photovoltaic cells - Arof, Abdul Kariem; Buraidah, M.H.; Teo, L.P.; Majid, S.R.; Yahya, Rosiyah; Taha, R.M. (Hindawi Publishing Corporation, 2010)
The membranes 55 wt. chitosan-45 wt. NH 4 I, 33 wt. chitosan-27 wt. NH 4 I -40 wt. EC, and 27.5 wt. chitosan-22.5 wt. NH 4 I -50 wt. buthyl-methyl-imidazolium-iodide (BMII) exhibit conductivity of 3.73Ã 10 -7, 7.34Ã 10 -6, and 3.43Ã 10 -5 S cm -1, respectively, at room temperature. These membranes have been used in the fabrication of solid-state solar cells with configuration ITO/ TiO 2 /polymer electrolyte membrane/ITO. It is observed that the short-circuit current density increases with conductivity of the electrolyte. The use of anthocyanin pigment obtained by solvent extraction from black rice and betalain from the callus of Celosia plumosa also helps to increase the short-circuit current.